2017
DOI: 10.1002/2211-5463.12356
|View full text |Cite
|
Sign up to set email alerts
|

High expression of PALB2 predicts poor prognosis in patients with advanced breast cancer

Abstract: PALB2 mutation is associated with increased breast cancer risk; however, PALB2 mutation is rare in sporadic breast cancer cases and little is known about PALB2 expression in breast cancer. Here, we evaluated the prognostic effects of PALB2 with tissue microarray specimens of 117 female breast cancer patients, and determined the potential underlying mechanisms in cell models. In immunohistochemical analysis, we found increased expression of PALB2 in breast cancer tissues compared with the adjacent normal ductal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 19 publications
2
10
0
Order By: Relevance
“…PALB2 acts as a tumor suppressor protein by mediating DNA repair and thereby suppressing genome instability [51]. In addition, its overexpression in tissue has recently been linked to a worse outcome in patients with MBC [52]. We found similar results on CTCs concerning patients' outcomes and found higher expression after one cycle of therapy, which might be induced to promote DNA repair.…”
Section: Discussionsupporting
confidence: 69%
“…PALB2 acts as a tumor suppressor protein by mediating DNA repair and thereby suppressing genome instability [51]. In addition, its overexpression in tissue has recently been linked to a worse outcome in patients with MBC [52]. We found similar results on CTCs concerning patients' outcomes and found higher expression after one cycle of therapy, which might be induced to promote DNA repair.…”
Section: Discussionsupporting
confidence: 69%
“…As EMT was the most prominent signaling pathway associated with decreased OS, the expression levels of certain EMT genes in PDAC cells were assessed. Consistent with the GSEA results, PALB2-knockdown affected the expression levels of Slug, Zeb1 and vimentin, which was also consistent with a previous study ( 29 ). However, the extent to which the other significantly associated signaling pathways contribute to the decreased OS of patients with high PALB2 expression requires further investigation.…”
Section: Discussionsupporting
confidence: 92%
“…Upregulated BRCA2 expression predicts a poor prognosis in patients with breast carcinoma ( 28 ). Similarly, elevated PALB2 expression is associated with poor clinical outcomes in patients with advanced breast carcinoma ( 29 ). However, independent research has indicated no association between PALB2 expression and breast cancer prognosis ( 30 ), and therefore additional studies are required to clarify this interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Literature study shows that the following proteins are in close association with BC, like FGFR2 [20], CTLA4 [10], MREII [18], BRAD1 [15], PALB2 [22], p53R2 [23], CDK 8 [6], CDK 4/6 [32], AKT1 [35], BRD4 [42], MDM2 [12], BRCA 1 and 2 [9], and RAD51 [24]. The 3D structure proteins and their respective protein data bank (PDB) Ids are given in Table 1.…”
Section: Selection Of Proteins For Dockingmentioning
confidence: 99%